The potential for ozone depletion in the Arctic polar stratosphere - Brune, W. H.; Anderson, J. G.; Toohey, D. W.; Fahey, D. W.; Kawa, S. R.; Poole, L. R. (1991)
The nature of the Arctic polar stratosphere is observed to be similar in many respects to that of the Antarctic polar stratosphere, where an ozone hole has been identified. Most of the available chlorine (CHl and ClONO2) was converted by reactions on polar stratospheric clouds to reactive ClO and Cl2O2 thoroughout the Arctic polar vortex before midwinter. Reactive nitrogen was converted to HNO3, and some, with spatial inhomogeneity, fell out of the stratosphere. These chemical changes ensured characteristic ozone losses of 10 to 15 percent at altitudes inside the polar vortex where polar stratospheric clouds had occurred. These local losses can translate into 5 to 8 percent losses in the vertical column abundance of ozone. As the amount of stratospheric chlorine inevitably increases by 50 percent over the next two decades, ozone losses recognizable as an ozone hole may well appear.